2017
DOI: 10.1044/2016_jslhr-h-16-0119
|View full text |Cite
|
Sign up to set email alerts
|

Speech Recognition in Adults With Cochlear Implants: The Effects of Working Memory, Phonological Sensitivity, and Aging

Abstract: Purpose: Models of speech recognition suggest that "topdown" linguistic and cognitive functions, such as use of phonotactic constraints and working memory, facilitate recognition under conditions of degradation, such as in noise. The question addressed in this study was what happens to these functions when a listener who has experienced years of hearing loss obtains a cochlear implant. Method: Thirty adults with cochlear implants and 30 agematched controls with age-normal hearing underwent testing of verbal wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(92 citation statements)
references
References 70 publications
4
75
1
3
Order By: Relevance
“… 7 , 8 , 9 The role that working memory plays in speech skills among adult CI users has received some attention with regard to word and sentence recognition and sentence comprehension, but remains poorly understood. 10 , 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
“… 7 , 8 , 9 The role that working memory plays in speech skills among adult CI users has received some attention with regard to word and sentence recognition and sentence comprehension, but remains poorly understood. 10 , 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
“…By contrast, we did not find a significant correlation between MLR features and speech recognition abilities in the present study. Speech perception relies on an interactive process between linguistic, cognitive, and social information, where a vast neural network contributes to the analysis of the different aspects of the speech stimulus (Moberly et al, 2017;Alemi et al, 2018). Therefore, it is perhaps not surprising that we could not find any evidence linking speech perception abilities to a single electrophysiological metric that is likely driven by a minority of these processes.…”
Section: Evaluating the Relationship Between Mlrs And Speech Recognitmentioning
confidence: 89%
“…Although it has been documented that experience with CI leads to a significant improvement in speech perception ability, especially during the first year of CI use (Blamey et al, 2013;Moberly et al, 2017), it does not imply that objective MLR measures are necessarily directly related to this ability. To our knowledge, only one study to date has shown a significant correlation between interelectrode amplitude variations (and latency measures) with speech perception scores (Groenen et al, 1997).…”
Section: Evaluating the Relationship Between Mlrs And Speech Recognitmentioning
confidence: 99%
“…Conceptually, rehabilitation can be divided into two approaches, top-down or bottom-up [23]. Methods that focus on bottom-up procedures utilize materials relating specifically to the input signals possible via a CI, that is, how a signal is processed.…”
Section: Rehabilitation Approachmentioning
confidence: 99%
“…Thus, cognitive factors play a large role in the wide variance seen in performance scores obtained by the adult CI population. Optimizing a personalized rehabilitation strategy must take into consideration the cognitive dynamics of speed of processing, working memory, and attention and executive function [23].…”
Section: Synthetic-cognitive Training (Top-down)mentioning
confidence: 99%